Therapeutic potential of trametinib to inhibit the mutagenesis by inactivating the protein kinase pathway in non-small cell lung cancer. Issue 1 (2nd January 2019) - Jeanson, Arnaud; Boyer, Arnaud; Greillier, Laurent; Tomasini, Pascale; Barlesi, Fabrice
ABSTRACT: Introduction :Mitogen-activated protein kinase (MAPK) pathway is known to be involved in the tumorigenesis of cancer cells including non-small cell lung cancer (NSCLC) and kinases involved in this pathway are frequently mutated. The development of new targeted therapies in cancer has led to the evaluation of MEK-inhibitors. Areas covered : This article reviews different studies using trametinib alone, in combination with other targeted therapies or associated with other non-targeted therapies in NSCLC, with a focus on KRAS mutant and BRAF mutant NSCLC. Expert commentary : Trametinib demonstrated activity in association with a BRAF inhibitor when BRAF was mutated. The combination of trametinib and dabrafenib has been approved for this population of BRAF mutant NSCLC patients. For KRAS mutant NSCLC, the combination of trametinib with chemotherapy has showed promising results and should be further assessed. Several clinical trials are ongoing, assessing trametinib in combination with other targeted therapies. In addition, preclinical studies suggest a synergistic effect of trametinib in combination with immune checkpoint inhibitors and such combinations should be studied in clinical trials.